(untitled) (Polis (Santiago), 2022)
In the context of the "turn to the right", neoliberal governments took office in some South American countries, including Argentina, Brazil, Ecuador, Uruguay, and the coup in Bolivia. The case of Argentina is paradigmatic: The markedly neoliberal profile of the government of Mauricio Macri (2015-2019) seemed to follow the dynamics of the shift to the right. However, despite the immense support of the mass media, the judiciary, important economic corporations, and multilateral organizations of credit, like the International Monetary Fund (IMF), the government lost the presidential elections of 2019. In this paper we analyze the political cycle erected between 2015 and 2019, concentrating on the dynamics of social mobilization, especially regarding its actors, demands, and repertoires The argument we propose is that the turn to the right was left unfinished due to a situation of “impossible tiebreaker” around neoliberalism. Social mobilization played a central role, not only in terms of street resistance but also because it became a space for political-party convergence, crystallized in the Frente de Todos. In methodological terms, we follow a mixed and multi-method strategy.